The knowledge of undergraduate dental students and dentists about antibiotic prophylaxis in patients at risk for infective endocarditis - Ana Paula Silva GANGÁ; Natália Bermond ARPINI; Tatiany Pimentel FERREIRA; Arlinda Lúcia Zocatelli CALENZANI; Paula Sampaio de Mello ASSIS (Faculdade São Leopoldo Mandic, 2020)
ABSTRACT Infective Endocarditis (IE) is an infection of the endocardial surface of the heart that is caused by fungi, bacteria or viruses. The high mortality and morbidity rates of IE have encouraged the adoption of preventive strategies. This study investigated the knowledge on the prevention of IE among 2nd, 3rd and 4th-year undergraduate dental students at the Escola Superior São Francisco de Assis (ESFA) and among dentists working in the municipality of Santa Teresa, ES, Brazil. Objective: The rationale for this study was to identify the gaps in their knowledge and raise awareness on the topic. Methods: The study was previously approved by the Research Ethics Committee. The sample consisted of dental students who had completed the Pharmacology for Dentistry course at the ESFA, totaling 35 2nd-year students, 29 3rd-year students, and 36 4th-year students. Thirty dentists registered in the Regional Council of Dentistry of Espírito Santo state, who were working in the municipality of Santa Teresa, ES, Brazil, were also included. All participants were given a questionnaire containing six objective and four subjective questions to assess their knowledge regarding the definition of IE, high-risk patients, dental procedures known to cause bacteremia, recommended dosage regimens for high risk patients, and additional care in the assistance of these patients. The questionnaires' responses were reviewed following the American Heart Association (AHA) guidelines for disease prevention published in 2007. Results: The analysis of the results revealed a low rate of correct responses among students and dentists. The questions with the lowest rate of correct responses were those addressing the identification of patients at high risk for heart conditions and the dental procedures known to cause bacteremia, with no significant differences between the four groups analyzed (P > 0.05). Third-year dental students presented a frequency of correct responses significantly lower than that of the other groups (P < 0.001), which did not differ from each other. To conclude, all participants demonstrated poor knowledge about the topic, particularly 3rd-year dental students. Conclusion: These results reinforce the need for informative measures to raise awareness and improve the quality of dental care provided to the population.